Protein kinase D regulates basolateral membrane protein exit from trans-Golgi network - Yeaman, Charles (2004)
Protein kinase D (PKD) binds to diacylglycerol (DAG) in the trans-Golgi network (TGN) and is activated by trimeric G-protein subunits βγ. This complex then regulates the formation of transport carriers in the TGN that traffic to the plasma membrane in non-polarized cells. Here we report specificity of different PKD isoforms in regulating protein trafficking from the TGN. Kinase-inactive forms of PKD1, PKD2 and PKD3 localize to the TGN in polarized and non-polarized cells. PKD activity is required only for the transport of proteins containing basolateral sorting information, and seems to be cargo specific.